Kesetaraan Gender Dalam Islam: Reinterpretasi Kedudukan Perempuan - Fajrul Islam Ats-Tsauri (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Primary mission of Islam teaching are realizing prosperity to human being and liberating them from all form of subordinate and injustice. Therefore, we need to reevaluate and questioning interpretation to Islamic teaching that inappropriate with justice and human rights values, example marginalizing women and gender inequality. Failure to interpreting al-Qur’an and Hadis will result discriminative woman fiqh. It’s because patriarchy and misogynist understanding because authoritarianism phenomena, reader arbitrary reading to religious texts, mainly by puritans. There’s several thing to do to appropriating religious interpretation with humanity: first, interaction between writer, texts, and reader; second, contextual, comprehensive, and historic reading, also interpretation with holistic and inductive method.